A bibliography of writing on varieties of English, 1965-1983 - Viereck, Wolfgang (Varieties of English around the world, 1984)
After the growth of English and American dialectology since the 1930's and the expansion of sociolinguistics since the 1960's, the study of 'world English' has emerged in recent years to join these other disciplines. This bibliography is intended to reflect what has been achieved in this area and to serve as an indispensable research tool for further investigations. The bibliography is divided into three parts, each one is preceded by a preface which explains the procedures followed and each of the sections is followed by an index. It classifies the items according to specific areas, ethnic groups, or similar topics, and thus makes the bibliography much easier to handle for the user.